Longitudinal 2D strain can help diagnose coronary artery disease in patients with suspected non-ST-elevation acute coronary syndrome but apparent normal global and segmental systolic function. (1st June 2017) - Caspar, Thibault; Samet, Hafida; Ohana, Mickaël; Germain, Philippe; El Ghannudi, Soraya; Talha, Samy; Morel, Olivier; Ohlmann, Patrick
Abstract: Background: The clinical work-up of patients presenting with chest pain is a diagnostic challenge. We investigated the diagnostic performance of global (GLS) and territorial (TLS) longitudinal strain to predict coronary artery disease (CAD) in patients presenting with suspected non-ST-segment elevation acute coronary syndrome (NSTE-ACS) but apparent normal global and regional systolic function. Methods: 150 consecutive suspected NSTE-ACS patients were initially screened for inclusion ; 58 patients with normal LVEF (≥ 55%) and WMSI (= 1) were prospectively enrolled. Speckle-tracking echocardiography was performed on admission and all the patients underwent coronary angiography. CAD was defined as the presence of stenosis of > 50%. Results: CAD was present in 33 patients (57%). LVEF was 60.7 ± 4.6% in group 1 (CAD) and 61.1 ± 5.0% in group 2 (no CAD). Global longitudinal strain (GLS) was altered in group 1 (− 16.7 ± 3.4%) as compared to group 2 (− 22.4 ± 2.9%, p < 0.001). ROC curve analysis showed a high diagnostic value of GLS for the prediction of CAD (AUC = 0.92 [0.84–1.00], p = 0.0001). TLS was able to discriminate between coronary stenosis in the LAD, LCX or RCA. Conclusions: Longitudinal 2D strain has a good diagnostic value and can efficiently localize the culprit lesion in patients presenting with NSTE-ACS but apparent normal global and regional systolic function. Highlights: 2D speckle-tracking can help the diagnostic work-up of patients with acute chest pain. In patients with suspected NSTE-ACS and no wall motion abnormalities, GLS is a good parameter to identify CAD. Territorial longitudinal strain might be helpful to localize the culprit lesion.